Ball data analysis in professional male tennis players` ground strokes - focused on difference of ball placement and position - Murakami, S.; Kashiwagi, R.; Okamura, S.; Takahashi, H. (Science and Racket Sports VI, 2019)
There has been a great discussion about ball placement of groundstrokes. It is broadly known that cross court shot is rally ball and down the line shot is offensive shot. However, it was not the evaluation based on objective values in which ball data as speed and ball spin rates were recorded. In recent years, it can record ball data as ball speed, spin rates, and net clearance by a new instrument. The main aim of this study was to clarify a way of how hitting by the difference of ball placement in professional players. The participants were two professional male tennis players in Japan. Two players played the game two sets. Ball data were collected by ball movement analysis system Trackman tennis radar. As the results, ball data by types of ball placement (Cross court, Center and Down the line) in player A were not significantly different on each position (Forehand: Right-Half, Left Half; Backhand). It suggests that high performance players can hit the ball accordingly without changing swing speed. Furthermore, it has a possibility that down the line shot and inside in shot are risky as it is generally said from the perspective of ball trajectory.